Advances in research on classroom dialogue: learning outcomes and assessments. (April 2017) - van der Veen, Chiel; van Oers, Bert
Abstract: The goal of this special issue is to examine how certain modes of classroom dialogue might contribute to students' learning outcomes. The articles in this special issue share the idea of classroom talk as a problem-oriented dialogue. In other words, an interactional configuration based on exchanges among students and teachers that go beyond the predominantly monologic approaches of classroom talk. In each of the contributions to this special issue, different types of learning outcomes were studied as a result of specific ways of orchestrating classroom dialogue. All in all, the studies in this special issue yield a picture of the field as a productive research area: they provide evidence for the plausibility of the assumption that dialogic orchestrations of classroom talk may produce various desired learning and developmental outcomes in students, depending on what outcomes we want to articulate, and how they are assessed. Although the studies in this special issue yield promising results for future improvements of classroom practice more (preferably longitudinal) research is required. Highlights: This special issue examines how classroom dialogue contributes to student learning. Dialogic orchestrations of classroom talk may produce desired learning outcomes. Assessment of the learning outcomes of classroom dialogue is important. Advances in research have been made, but more longitudinal research is required.